Analisis Kemampuan Spasial Matematis Ditinjau dari Perbedaan Gender Siswa Kelas VIII - Kamila Ismi; Kusaeri Al; Kiki Riska Ayu Kurniawati; Habib Ratu Perwira Negara (Journal Focus Action of Research Mathematic (Factor M), 2021)
This study aims to describe the students' mathematical spatial abilities based on gender differences in the VIII grade Mathematics subject. The population in this study were eighth grade students of SMP Negeri 2 Praya. The subjects of this study were 4 students from 27 students of class VIII with the provisions of 2 male gender subjects and 2 female gender subjects who had the highest mathematical spatial ability of all students. The instruments used in this study were tests of mathematical spatial abilities and interviews. Technical data analysis is done by reducing data, presenting data, and drawing conclusions. Checking the validity of the data using triangulation techniques. The results showed that the spatial visualization ability of male subjects and female subjects had the same ability as indicated by the ability to determine the composition of an object after being manipulated in its position and shape. Meanwhile, in solving problems related to spatial orientation and spatial relations, male subjects are more dominant in using their spatial abilities than female subjects.